ERGO-PSYCHOPHYSIOLOGY DECREASING PHYSIOLOGICAL RESPONSES, INCREASING ALERTNESS, WORK ABILITY AND WORK ENGAGEMENT AT THE ACCOUNTING DEPARTMENT OF BALI HYATT HOTEL, DENPASAR - Indah, Luh Made; Pangkahila, J. A.; Manuaba, I.B. Adnyana; Tirtayasa, I Ketut (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 1 No 2 (2015): Volume 1 No 2 Desember 2015, 2015)
Employee's performance can be determined from physiological responses, alertness, work abilityand work engagement. The performance can be achieved when employees are able to adjust the capacity to the existing task demands, once is in accounting department. This department requires the ability to adjust the capacity of employees physiologically and psychologically with the tasks demands, one of the tasks was maintaining financial balance by using a computer. Employees work comfortably, safely, healthy thus increasing productivity. The working conditions need to be improved to prevent fatigue, complaints, discomfort, injury, stress, until disorder/disease that affects the company performance. It is to apply ergonomics interventions with emphasis on the psychological approach or Ergo-Psychophysiology.Experimental studies have been carried out with treatment by subject design to the 17 employees at accounting department of Bali Hyatt Hotel, Denpasar. Sample performance observed when working in conventional condition (first period) and when working with treated Ergo-Psychophysiology (second period). Employee performance data between the two periods compared and analyzed by t-paired test at the significance level of 0.05.The data results showed that a decreased in the physiological response based on the decrease of fatigue was 22.18 % and musculoskeletal complaints was 9.08 %. The alertness of employee increased based on increase of pace of work was 12.73 %, an increase of accuracy was 9.52 % and increased of constancy was 21.62 %. An increased of work ability was 7.57% and an increased of work engagement was 16.73 % (p<0.05). There was no significance result for workload based on the working pulse (p>0.05). The results showed that the Ergo- Psychophysiological influenced employee performance based on physiological responses, alertness, work ability and work engagement, although the workload is not affected. This suggests that task demand of employment in the accounting department is more mental abilities than physical activity.It was concluded that the Ergo-Psychophysiology decrease the physiological response based on the decrease in fatigue and musculoskeletal complaints. Ergo-Psychophysiology also increases alertness, work ability and work engagement. It is suggested to support on mental working condition in the accounting department.
Keywords: Ergo-Psychophysiology, Physiological Responses, Alertness, Work Ability, Work Engagement